Engaging new refugee in Australian communities at risk for chronic hepatitis B infection into care: A peer‐educator intervention. (10th July 2018) - Sievert, Katherine; O'Neill, Paul; Koh, Youlin; Lee, Jia‐Hui; Dev, Anouk; Le, Suong
Abstract: Chronic Hepatitis B (CHB) infection and subsequent liver complications are rising in prevalence in Australia due to increased migration from endemic regions. Nearly 50% of all those living with CHB in Australia are undiagnosed, leading to missed opportunities for liver cancer and cirrhosis prevention. Health literacy around CHB among refugee communities such as Afghan, Rohingyan, and Sudanese populations (all with a high prevalence of CHB) is low, partly due to a paucity of targeted health promotion programmes; despite the release of the Victorian Hepatitis B Strategy (2016–2020). We developed a peer‐education intervention in these three communities to deliver CHB focused radio programmes and community forums in their own language, following a needs assessment consisting of semistructured interviews and surveys. Effectiveness of this intervention was measured through paired comparison of disease‐knowledge assessment pre and post forum. Community forums were held between 2015 and 2016, with 25 attendees at the Rohingyan forum (68% male), 10 attendees at the Afghan forum (90% male) and 0 attendees at the Sudanese forum. Participants demonstrated a significant improvement in CHB knowledge between pre‐ and post‐forum surveys ( p ‐value < 0.05). A peer‐educator approach was a cost‐effective health promotion strategy in building CHB knowledge and dispelling misconceptions within the Afghan and Rohingya communities. There were significant barriers in the engagement of the South Sudanese community, which will inform future strategies for health promotion.